Swing kinematics of male and female skilled golfers following prolonged putting practice - Horan, S. A.; Evans, K.; Morris, N. R.; Kavanagh, J. J. (Journal of Sports Sciences, 2014)
Given that males and females respond differently to endurance-based tasks, prolonged putting practice may provide an avenue to examine gender-related differences in golf swing kinematics. The aim of this project was to determine if 40 min of putting affects thorax and pelvis kinematics during the full swing of males and females. Three-dimensional trunk kinematics were collected during the swings of 19 male (age: 26 ± 7 years, handicap: 0.6 ± 1.1) and 17 female (age: 24 ± 7 years, handicap: 1.4 ± 1.7) golfers before and after 40 min of putting. Angular displacement at address, top of backswing and ball contact for the pelvis, thorax, and pelvis-thorax interaction were calculated, in addition to the magnitude of peak angular velocity and repeatability of continuous segment angular velocities. Female golfers had less pelvis and thorax anterior-posterior tilt at address, less thorax and thorax-pelvis axial rotation at top of backswing, and less pelvis and thorax axial rotation and pelvis lateral tilt at ball contact pre- to post-putting. Analysis of peak angular velocities revealed that females had significantly lower thorax-pelvis lateral tilt velocity pre- to post-putting. In conclusion, an endurance-based putting intervention affects females` thorax and pelvis orientation angles and velocities to a greater extent than males.